2018
DOI: 10.1007/s00253-018-9433-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of microbes in the orchestration of plants’ resistance to biotic stress: a disease management approach

Abstract: The struggle for survival is a natural and a continuous process. Microbes are struggling to survive by depending on plants for their nutrition while plants on the other hand are resisting the attack of microbes in order to survive. This interaction is a tug of war and the knowledge of microbe-plant relationship will enable farmers/agriculturists improve crop health, yield, sustain regular food supply, and minimize the use of agrochemicals such as fungicides and pesticides in the fight against plant pathogens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(72 citation statements)
references
References 140 publications
(134 reference statements)
0
58
0
7
Order By: Relevance
“…The response to biotic stress can activate systemic acquired resistance (SAR) gene expression due to pathogen attack, or the interaction with beneficial microorganisms can activate the immunity system of the plant (induced systemic resistance (ISR)) [ 67 ]. The pathogen attacks cause biotic stress to plants, which results in the production of various reactive oxygen containing species (oxygen, hydroxyl radicals, hydrogen peroxide, superoxide molecules; ROS) and nitric oxide (NO), which are the most active in the alkaline pH, which results in the rise of cytosolic calcium ion concentration and closure of stomata [ 68 , 69 ].…”
Section: Phenolic Acids In Plantsmentioning
confidence: 99%
“…The response to biotic stress can activate systemic acquired resistance (SAR) gene expression due to pathogen attack, or the interaction with beneficial microorganisms can activate the immunity system of the plant (induced systemic resistance (ISR)) [ 67 ]. The pathogen attacks cause biotic stress to plants, which results in the production of various reactive oxygen containing species (oxygen, hydroxyl radicals, hydrogen peroxide, superoxide molecules; ROS) and nitric oxide (NO), which are the most active in the alkaline pH, which results in the rise of cytosolic calcium ion concentration and closure of stomata [ 68 , 69 ].…”
Section: Phenolic Acids In Plantsmentioning
confidence: 99%
“…Research on the development of the disease cycle, epidemiology, host resistance and biological control are fundamental in order to develop new eco-friendly alternatives for managing crop diseases. (Enebe & Babalola, 2019; Sánchez-Martín & Keller, 2019). In this scenario, V. dahliae is a particularly challenging pathogen, due to its wide host range and its capacity of developing microsclerotia that assures it stability in soils as active inoculum for long periods(Wheeler & Johnson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, induced systemic resistance (ISR), potentiated by numerous strains of nonpathogenic microorganisms such as plant growth-promoting rhizobacteria (PGPR), is another route to boost the broad-spectrum immunity in plants [93,99,100]. Many studies have shown the efficacy of PGPR to induce ISR such as in tomato to defend Phelipanche aegyptiaca [101] and Pseudomonas syringae [102]; cotton against Macrophomina phaseolina (Tassi) [71]; tobacco to resist Tobacco mosaic virus [103]; mung bean to protect against Macrophomina phaseolina [104]; rice against Xanthomonas campestris [105]; and tomato to defend Ralstonia solanacearum [106].…”
Section: Biotic and Abiotic Stresses Induced Host Defensementioning
confidence: 99%